Relationship between kinematic factors and countermovement jump height in trained track and field athletes - Gonzales-Badillo, J. J.; Marques, M. C. (The Journal of Strength and Conditioning Research, 2010)
Countermovement jump (CMJ) has been extensively used in training, yet kinematic data for a large sample of trained athletes are limited. The aim of this study was to determine the relationship between kinematic factors of CMJ height in a large sample of trained track and field athletes. Forty-eight adult athletes performed 3 maximal CMJ-weighted jumps while ground reaction forces were sampled using a force platform synchronized with a linear transducer. The CMJ height presented significant relations with both eccentric (descending) and concentric (ascending) phases. In addition, strong correlations were observed between CMJ performance and the peak power produced during the concentric phase (r = 0.812-0.851) and with the average power generated in the same phase (r = 0.829-0.870). Finally, maximal negative velocity was low to moderate in its association with CMJ performance (r = 0.57-0.65). The present data contribute important knowledge concerning determinant factors of vertical jump performance that have not been analyzed in trained athletes. As predictors, it is important to observe high values of correlation between the force produced during the concentric and eccentric phases with the height of all the CMJ trials. In this way, our study confirms previous findings in which peak power was shown to be the best predictor of CMJ height. Nevertheless, the moderate but significant predictive value of negative velocity was even more noticeable.